Staff Perspectives on a Tablet-Based Intervention to Increase HIV Testing in a High Volume, Urban Emergency Department - Aronson, Ian David; Guarino, Honoria; Bennett, Alexander S.; Marsch, Lisa A.; Gwadz, Marya; Cleland, Charles M.; Damschroder, Laura; Bania, Theodore C. (Frontiers in Public Health, 2017)
Emergency Departments (EDs) frequently serve people who have limited, if any, additional interactions with healthcare, yet many ED patients are not offered HIV testing, and those who are frequently decline. ED staff (n=13) at a high volume urban ED (technicians, nurses, physicians, and administrators) were interviewed to elicit their perspectives on the feasibility and acceptability of a tablet-based intervention designed to increase HIV test rates among patients who initially decline testing. Content-based thematic analysis of semi-structured interviews indicated overall support for interventions to increase HIV testing, but a lack of available staff resources emerged as a potential barrier to widespread implementation. Also, some ED staff questioned whether it was appropriate to shift responsibility for public health services, such as HIV testing, to the ED instead of a primary care setting. Although tablet-based interventions have been shown effective in high volume ED settings, and can potentially increase HIV test rates among hard-to-reach populations, additional effort is now required to better integrate this type of intervention into existing workflows.